Annexin A1 regulates hormone exocytosis through a mechanism involving actin reorganization. - McArthur, S; Yazid, S; Christian, H; Sirha, R; Flower, R; Buckingham, J; Solito, E (2009)
The glucocorticoid-regulated protein annexin A1 is a potent inhibitor of hormone exocytosis in the neuroendocrine system, acting in a paracrine/juxtacrine manner. The signaling mechanism employed by annexin A1 in this process is uncertain, although we have recently presented evidence for a role of the formyl peptide receptor in vivo. We sought to characterize the mechanism of action of annexin A1 on exocytosis using the release of adrenocorticotrophin from the corticotroph-like cell line AtT20 as an in vitro model system. Through the comparison of adrenocorticotrophin release from cells expressing either wild-type annexin A1 or mutant forms, we show a critical involvement of phosphorylation on serine 27 and 45 in the translocation of the protein to the membrane and its inhibitory action on exocytosis. Moreover, we show, for the first time, that annexin A1-dependent inhibition of adrenocorticotrophin release involves the enhancement of actin polymerization to prevent exocytosis via formyl peptide receptor and Rho kinase signaling pathways. This finding has significant implications for the inhibitory actions of annexin A1 on exocytosis in other endocrine and immune contexts.